KEPUASAN PETANI PADI SAWAH TERHADAP KINERJA PENYULUH PERTANIAN DI DESA KOPI KECAMATAN BINTAUNA KABUPATEN BOLAANG MONGONDOW UTARA - Mona Meily Soleh; Oktavianus Porajow; Noortje Marselianie Benu (AGRI-SOSIOEKONOMI, 2020)
This study aims to analyze the level of farmer satisfaction with the performance of agricultural instructors in Kopi Village, Bintauna Subdistrict, North Bolaang Mongondow Regency. The study was conducted from January 2020 to April 2020. Primary data were obtained through direct interviews with 29 respondents using questionnaires and secondary data obtained from the Village Village government office. The sampling method is done by using the purposive sampling method, which is intentional sampling. Based on the results of the study it can be concluded that the satisfaction of farmers to the performance of agricultural extension workers in the whole Coffee Village is satisfied. This is evidenced by the results of the farmer satisfaction index value obtained by 91.35 percent.